2006
DOI: 10.1063/1.2195383
|View full text |Cite
|
Sign up to set email alerts
|

Formation of laser plasma channels in a stationary gas

Abstract: The formation of plasma channels with nonuniformity of about ± 3.5% has been demonstrated. The channels had a density of 1.2×10 19 cm -3 with a radius of 15 µm and with length ≥ 2.5 mm. The channels were formed by 0.3 J, 100 ps laser pulses in a nonflowing gas, contained in a cylindrical chamber. The laser beam passed through the chamber along its axis via pinholes in the chamber walls. A plasma channel with an electron density on the order of 10 18 -10 19 cm -3 was formed in pure He, N 2 , Ar, and Xe. A unifo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Energy losses are believed to occur because of this LPI, energy absorption into the window material, and from window material mixing into the fuel (which leads to enhanced radiation loss). [5][6][7][8][9][10] To reduce these losses, the LEH window could be removed before the preheating laser passes through the LEH. This concept of early-time window removal is referred to as "Laser Gate".…”
Section: Fig 1 a Schematic Representation Of The Three Phases Ofmentioning
confidence: 99%
“…Energy losses are believed to occur because of this LPI, energy absorption into the window material, and from window material mixing into the fuel (which leads to enhanced radiation loss). [5][6][7][8][9][10] To reduce these losses, the LEH window could be removed before the preheating laser passes through the LEH. This concept of early-time window removal is referred to as "Laser Gate".…”
Section: Fig 1 a Schematic Representation Of The Three Phases Ofmentioning
confidence: 99%
“…Those targets were allow possibility to develop capillary discharge EUV laser used in many experiments, such as holography [13], interferometry [14], lithography [15] and microscopy [16]. There are many other possible application of capillary targets, such as plasma channel formation [17], a medium for high energy electron acceleration [18] or amplification of X-ray pulses, [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, more detailed references to the literature describing the state of research on this problem can also be found. However, laboratory investigations of plasma channels formation in stationary gas [5] are of great importance nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…Impulses of high power and short duration are utilized for the formation of plasma channels in gaseous media [4,5]. A method of plasma creation based on the superelastic electron heating effect under the photoexcitation by laser radiation of resonant atoms [6][7][8][9] can be considered as an alternative to this method.…”
Section: Introductionmentioning
confidence: 99%